Treatment of carpometacarpal and middle carpal joint hyperextension injuries with partial carpal arthrodesis using a cross pin technique: 21 cases - Haburjak, J. J.; Lenehan, T. M.; Davidson, C. D.; Tarvin, G. B.; Carlson, K. R.; Hayes, A. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The cross-pin technique presented here was technically easy to perform, allowed latitude in pin placement, had manageable post-operative issues and allowed for facilitated pin removal. Objective patient inclusion criteria remain to be established.
Keywords: Arthrodesis; partial; canine